Excellent electromagnetic shield derived from MWCNT reinforced NR/PP blend nanocomposites with tailored microstructural properties. (15th September 2019) - Sharika, T.; Abraham, Jiji; Arif P, Mohammad; George, Soney C.; Kalarikkal, Nandakumar; Thomas, Sabu
Abstract: Blends of polypropylene (PP) and natural rubber (NR) with different loadings (1, 3, 5 &7 wt%) of multiwalled carbon nanotubes (MWCNTs) were prepared by melt blending process to design a nanocomposite with tunable electromagnetic interference (EMI) shielding performance. Scanning electron microscopy (SEM) studies show that the addition of MWCNTs changes the droplet morphology into quasi co-continuous morphology for PP/NR 80/20 (wt/wt) blend system. However there is a refinement in the co-continuous morphology of PP/NR (50/50) by the addition of MWCNTs. The effects of the blend morphology and selective localization of MWCNTs on the dielectric, electrical properties and EMI shielding performance were systematically investigated. The largely enriched dielectric performance originates from the interfacial polarization of MWCNTs within the polymer. It is understood that the shielding performance significantly enhanced due to the selective localization of MWCNTs in the NR phase that provided high conductivity and heterogeneous dielectric media with multiple interfaces. The blend nanocomposites show a shielding effectiveness of ca.29 dB at 3 GHz for 7 wt% of MWCNT loading. Graphical abstract: Image 1